Evaluation of Satisfaction with Anesthesia Care by Appliance of Heidelberg’s Questionnaire in a Portuguese Surgical Population - Cunha, Ana; Barbosa, Joselina; Costa, Catarina; Ferreira, Maria; Mourão, Joana (Journal of the Portuguese Society of Anesthesiology, 2014)
Background: Our aim is to apply the questionnaire “Heidelberg Peri-Anesthetic Questionnaire”, on patients’ receiving elective procedures in vascular, plastic and general surgery and confirm its psychometric qualities, as well as study the influence of their social-demographic and clinical characteristics on satisfaction outcome. Materials and Methods: One hundred and ninety two patients were given a 32-item consensus version questionnaire by a member of the study who did not intervene in the patient’s anesthesiology team. This questionnaire consisted of 5 dimensions (D1- Team, D2- Fear/Anxiety, D3- Loneliness, D4- Discomfort). Questionnaire delivery occurred between July and October 2013. Results: The results revealed that all items contribute to instrument internal consistency (Cronbach’s α 0.614-0.826). The highest satisfaction was associated with Team Dimension (D1) and the lowest satisfaction with Discomfort (D4). After a multiple linear regression analysis, gender showed influence on Discomfort (D4) and Anxiety/Fear (D2), with men showing less fear and less discomfort. Also, less literate patients were more satisfied with D1 as well as patients with pre-anesthetic consult. Discussion: We established an important correlation between pre-anesthesia consult and D1 indicating that these patients were more satisfied probably due to communication and better doctor-patient relationship. We didn’t find any significant effect of type and duration of anesthesia, surgical service, surgical risk and ASA physical state. Conclusions: Globally we can determine that patients were satisfied with their anesthesia care and this questionnaire could easily be used in a day-to-day basis and could give a reliable feedback on the anesthesiologists’ performance during perioperative period.